A new generic name, Semigothograptus, for Gothograptus? meganassa Rickards & Palmer, 2002, from the Silurian post-lundgreni Biozone recovery phase, and comparative morphology of retiolitids from the lowermost upper Homerian (upper Wenlock) - Kozłowska, Anna (Zootaxa, 2016)
Gothograptus? meganassa Rickards & Palmer, 2002 is assigned to a new genus Semigothograptus. New, well preserved material from the dubius/nassa Biozone (upper Homerian, Silurian) of the Bartoszyce IG-1 drill core Poland is described. This provides a new phylogenetic perspective on the evolution of post-lundgreni Event retiolitines. Semigothograptus meganassa is considered to be a descendant of Gothograptus nassa, although one of the most significant differences between these forms is the position of the nema, and narrow finite tubarium ending in an appendix in G. nassa. S. meganassa possesses looping meshes of the ancora umbrella recognised in Gothograptus, Papiliograptus, and Baculograptus and shares the common characters of all stratigraphical younger retiolitines. It is recognised that the S. meganassa is known from four terrains: Avalonia, Baltica, Bohemia, and Saxo-Thuringia. Analysis of the genicular hoods of nassa type, characteristic of Gothograptus nassa, Gothograptus kozlowskii, Semigothograptus meganassa, and Neogothograptus eximinassa, demonstrates their unique, solid bandage construction.